Monocrystal ternary positive electrode material and preparation method thereof

By covering the titanate ferroelectric nanomaterial on the substrate surface of the single crystal ternary positive electrode material, the problem of performance degradation of single crystal high-nickel positive electrode material during the first charge and discharge and subsequent cycles is solved, and the first-circuit Coulomb efficiency and cycle stability are achieved.

CN119920875APending Publication Date: 2025-05-02GUANGDONG MIC POWER NEW ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411907087.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The single crystal high-nickel cathode material does not fully exert its capacity during the first charge and discharge process, and its performance deteriorates rapidly due to interface degradation during the subsequent cycle.

Method used

The surface of the single-crystal ternary positive electrode material matrix is ​​coated with titanate ferroelectric nanomaterials to form an island-like cladding structure, reducing the loss of active lithium ions and improving the transmission efficiency of lithium ions.

Benefits of technology

The first-circle Coulomb efficiency and cycle stability of single-crystal ternary positive electrode material are significantly improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920875A_ABST
    Figure CN119920875A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery materials, and discloses a single-crystal ternary positive electrode material and a preparation method thereof. The single-crystal ternary positive electrode material comprises a single-crystal ternary positive electrode material matrix and a coating structure, the coating structure is a titanate ferroelectric nano material, and the titanate ferroelectric nano material is coated on the surface of the single-crystal ternary positive electrode material matrix. According to the ternary positive electrode material disclosed by the invention, the surface of the single-crystal high-nickel ternary positive electrode material matrix is coated with the titanate ferroelectric nano material in situ, so that the loss of active lithium ions of the high-nickel positive electrode material in the first-circle charge-discharge cycle process is reduced, and the first-circle coulombic efficiency of the high-nickel ternary material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and more specifically, to a single crystal ternary positive electrode material and a preparation method thereof. Background Art

[0002] Among the various components of lithium-ion batteries, the positive electrode material plays a vital role and largely determines the energy density and monomer cost of lithium-ion batteries. Among the many positive electrode materials, high-nickel layered oxide positive electrode material LiNi x Co 1-y M y O2 (x ≥ 0.8, M is Mn or Al) has attracted much attention due to its higher energy density and more balanced properties.

[0003] There are mainly two types of high-nickel positive electrode materials: single crystal and polycrystalline. Among them, single crystal high-nickel positive electrode materials have the advantages of high mechanical strength and good cycle stability, and have gradually become a hot research direction. However, single crystal high-nickel positive electrode materials still have many performance defects. First, single crystal materials have a relatively long ion transmission path. At the same time, the surface of the material is in contact with the air. The Li2O remaining from the solid-phase sintering reaction and the lattice oxygen on the surface will react with H2O and CO2 to generate Li2CO3, LiHCO3 and LiOH impurities. These reasons will seriously affect the capacity of the high-nickel positive electrode material during the first charge and discharge process and cause a large degree of capacity attenuation in subsequent cycles; secondly, during the cycle, the surface of the high-nickel material is in direct contact with the electrolyte, and the highly charged Ni on the surface 4+ It has high reactivity and easily reacts with organic / inorganic components in the electrolyte, causing serious degradation of the high-nickel material interface, hindering the transmission of lithium ions, and ultimately leading to rapid performance degradation. Summary of the invention

[0004] An object of the present invention is to provide a new technical solution for single crystal ternary positive electrode materials.

[0005] According to a first aspect of the present invention, a single crystal ternary positive electrode material is provided, which comprises a single crystal ternary positive electrode material matrix and a coating structure, wherein the coating structure is a titanate ferroelectric nanomaterial, and the titanate ferroelectric nanomaterial is coated on the surface of the single crystal ternary positive electrode material matrix.

[0006] Optionally, the coating structure is coated on the surface of the single crystal ternary positive electrode material substrate in an island shape, and the thickness of the coating structure is 1-100 nm.

[0007] Optionally, the chemical formula of the single crystal ternary cathode material is MTiO3@LiNi x Co y Mn zO2, where in terms of molar ratio, 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1 – x – y, and M is selected from at least one of Ba and Sr.

[0008] According to the second aspect of the present invention, there is provided a method for preparing a single-crystal ternary cathode material, and the preparation method includes the following steps:

[0009] (1) Mix the single-crystal hydroxide precursor and lithium hydroxide充分混合后置于管式炉内,在氧气气氛下烧结,冷却后得到单晶三元正极材料基体;

[0010] (2) Uniformly disperse the reactants of the titanate ferroelectric nanomaterial in an organic solvent, add the single-crystal ternary cathode material matrix and mix evenly, and then fully evaporate to dryness under a water bath heating and stirring environment to obtain a modified intermediate product;

[0011] (3) Sinter the modified intermediate product in a tube furnace, and obtain the single-crystal ternary cathode material after natural cooling. The surface of the single-crystal ternary cathode material is a coating structure of the titanate ferroelectric nanomaterial.

[0012] Optionally, in step (1), the chemical formula of the single-crystal hydroxide precursor is Ni x Co y Mn z (OH)2, in terms of molar ratio, 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1 – x – y, and the particle size distribution of the single-crystal hydroxide precursor is 10.0 μm ≤ d (50) ≤ 11.5 μm .

[0013] Optionally, the sintering in the oxygen atmosphere in step (1) is carried out in an oxygen-containing atmosphere in a two-stage sintering manner. The concentration of oxygen in the oxygen-containing atmosphere is not less than 95%. The two-stage sintering includes: first sintering at 500 - 600 °C for 4 - 6 h, and then sintering at 700 - 800 °C for 10 - 16 h. The rate of temperature increase and decrease during the two-stage sintering process is 1 - 5 °C / min.

[0014] Optionally, in step (2), the reactants of the titanate ferroelectric nanomaterial are a titanium-containing compound and an alkaline earth metal compound, and the organic solvent is an absolute ethanol solution.

[0015] Optionally, the titanium-containing compound is selected from at least one of TiO2, Ti(NO3)4, and Ti(BH4)2.

[0016] Optionally, the alkaline earth metal compound is selected from one or more of Ba(OH)2, BaCO3, Sr(OH)2, and SrCO3.

[0017] Optionally, in the titanium-containing compound and the alkaline earth metal compound, the molar ratio of titanium ions to alkaline earth metal ions is 1:1.

[0018] Optionally, the molar ratio of the sum of nickel ions, cobalt ions and manganese ions to titanium ions in the single crystal ternary positive electrode material satisfies 1:(0.5%-1.5%).

[0019] Optionally, in step (3), the calcination temperature is 240-280° C., the sintering heating rate is 1-5° C. / min, the sintering cooling process is natural cooling, and the sintering duration is 18-22 hours.

[0020] The single crystal ternary positive electrode material of the present invention reduces the loss of active lithium ions during the first cycle of the single crystal ternary positive electrode material by coating the surface of the single crystal ternary positive electrode material matrix with titanate ferroelectric nanomaterials, thereby improving the first cycle coulombic efficiency of the single crystal ternary positive electrode material.

[0021] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0023] Figure 1 This is a SEM image of the morphology and surface element composition of the single crystal ternary positive electrode material of Example 1 of the present invention.

[0024] Figure 2 This is a TEM image of the interface coating of the single crystal ternary positive electrode material of Example 1 of the present invention.

[0025] Figure 3 This is a PFM test result diagram of the single crystal ternary positive electrode material of Example 1 of the present invention.

[0026] Figure 4 It is an XRD phase characterization diagram of the single crystal ternary positive electrode material of Example 1 of the present invention and the material prepared in the comparative example.

[0027] Figure 5 It is a comparison chart of the capacity-voltage curves of the first cycle charge and discharge of the single crystal ternary positive electrode material of Example 1 of the present invention and the material prepared in the comparative example.

[0028] Figure 6 It is a comparison chart of the cycle curves of the single crystal ternary positive electrode material of Example 1 of the present invention and the material prepared in the comparative example.

[0029] Figure 7This is the first cycle charge and discharge capacity-voltage curve of the single crystal ternary positive electrode material of Example 2 of the present invention.

[0030] Figure 8 This is the cycle curve of the single crystal ternary positive electrode material of Example 2 of the present invention. DETAILED DESCRIPTION

[0031] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0032] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0033] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.

[0034] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0035] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0036] According to one embodiment of the present invention, a single crystal ternary positive electrode material is provided, the single crystal ternary positive electrode material comprises a single crystal ternary positive electrode material matrix and a coating structure, the coating structure can be selected from titanate ferroelectric nanomaterials, and the titanate ferroelectric nanomaterials are in-situ coated on the surface of the single crystal ternary positive electrode material matrix. Titanate-based materials have high polarization strength, good temperature stability, and significantly excellent ferroelectric properties. In addition, compared with ferroelectric materials containing heavy metals, titanate-based materials are more environmentally friendly and can reduce pollution to the environment.

[0037] Optionally, the coating structure belongs to island coating, and the titanate ferroelectric nanoparticles are coated on the surface of the single-crystalline ternary cathode material matrix in an island shape, and the thickness of the coating structure is 1-100 nm. The coating structure is ferroelectric nanomaterial particles. Since the thickness of the introduced ferroelectric nanomaterial is small, the particle size of the total ferroelectric nanomaterial in the coating structure layer is small and uniform, and the number of particles is also small, which is beneficial to improving the material performance in the later stage of cycling. The coating material itself is not an excellent lithium-ion conductor, and uniform coating will, to a certain extent, inhibit the ion transport during the charge and discharge process of the cathode material. Selecting to coat the surface of the cathode material matrix with ferroelectric-effect materials in an island shape can form specific lithium-ion transport channels along the boundaries of the coated particles, accelerating the ion transfer during the charge and discharge process.

[0038] Furthermore, the thickness of the coating structure is 6-80 nm. Since the thickness of the coating structure layer is small, it will not affect the compaction density of the prepared electrode sheet.

[0039] Optionally, the chemical formula of the single-crystalline ternary cathode material is MTiO3@LiNi x Co y Mn z O2, where in terms of molar ratio, 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1–x–y, and M is selected from at least one of Ba and Sr. When both Ba element and Sr element are selected, the BaTiO3 and SrTiO3 formed after coating can each play their advantages and achieve a better synergistic effect.

[0040] In the chemical formula of the single-crystalline ternary cathode material of the present invention, in terms of molar ratio, the proportion of nickel is more than 90%. Therefore, the single-crystalline ternary cathode material of the present invention belongs to the single-crystalline high-nickel ternary lithium battery cathode material.

[0041] According to the second aspect of the present invention, there is provided a preparation method of the aforementioned single-crystalline high-nickel ternary cathode material, and the preparation method includes the following steps:

[0042] (1) Mix the single-crystalline hydroxide precursor and lithium hydroxide充分混合后置于管式炉内,在氧气气氛下烧结,冷却后得到单晶三元正极材料基体;

[0043] (2) Uniformly disperse the reactants of the titanate ferroelectric nanomaterial in an organic solvent, add the single-crystalline ternary cathode material matrix and mix evenly, and then fully evaporate to dryness under a water bath heating and stirring environment to obtain a modified intermediate product;

[0044] (3) Place the modified intermediate product in a tube furnace for sintering, and naturally cool to obtain the single-crystalline ternary cathode material, and the surface of the single-crystalline ternary cathode material is the titanate ferroelectric nanomaterial coating structure.

[0045] Optionally, the single-crystalline hydroxide precursor described in step (1) can be prepared by oneself or purchased as a commercial finished product. The chemical formula of the precursor is Ni x Co y Mn z (OH)2, where the parameters should satisfy, in terms of molar ratio: 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1 – x – y. The particle size distribution of the single-crystalline hydroxide precursor is 10.0 μm ≤ d (50) ≤ 11.5 μm .

[0046] Optionally, the sintering in an oxygen atmosphere in step (1) is a two-stage sintering in an oxygen-containing atmosphere. The oxygen-containing atmosphere can be a mixture of oxygen and nitrogen. Further, the concentration of oxygen in the oxygen-containing atmosphere is not less than 95%.

[0047] Optionally, the sintering in step (1) is a two-stage high-temperature sintering, including:

[0048] The first sintering temperature is 500 - 600 °C, and the sintering time is 4 - 6 h;

[0049] The second sintering temperature is 700 - 800 °C, and the sintering time is 10 - 16 h.

[0050] During the two-stage sintering process of the present invention, the rate of temperature rise and fall is 1 - 5 °C / min. Further, to precisely control the temperature and reduce the influence of temperature instability on the sintering effect, the rate of temperature rise and fall of the sintering temperature of the present invention is controlled at 1 - 3 °C / min, preferably 2 °C / min.

[0051] Step (2) of the present invention is to perform a coating modification treatment on the single-crystalline high-nickel ternary cathode material matrix. The modification treatment is to in-situ coat a ferroelectric nanomaterial structure on the surface of the single-crystalline ternary cathode material matrix. First, the reactants of the ferroelectric nanomaterial need to be dispersed in an organic solvent. After the reactants of the ferroelectric nanomaterial are uniformly dispersed in the solvent, then the single-crystalline ternary cathode material matrix is added, and then it is fully evaporated under a water bath heating and stirring environment to obtain a modified intermediate product.

[0052] Optionally, the ferroelectric nanomaterial is a titanate ferroelectric nanomaterial. The reactants for forming the titanate ferroelectric nanomaterial are a titanium-containing compound and an alkaline earth metal compound. The organic solvent used is a common organic solvent, such as an anhydrous ethanol solution.

[0053] Optionally, in the titanium-containing compound and the alkaline earth metal compound, the molar ratio of titanium ions to alkaline earth metal ions is 1:1.

[0054] Optionally, the titanium-containing compound is selected from at least one of TiO2, Ti(NO3)4, and Ti(BH4)2.

[0055] Optionally, the alkaline earth metal compound is selected from one or more of Ba(OH)2, BaCO3, Sr(OH)2, and SrCO3.

[0056] Optionally, the molar ratio of the sum of nickel ions, cobalt ions and manganese ions to titanium ions in the single crystal ternary positive electrode material satisfies 1:(0.5%-1.5%). Further, the molar ratio of the sum of nickel ions, cobalt ions and manganese ions to titanium ions in the single crystal ternary positive electrode material is 1:1.

[0057] Step (3) of the positive electrode material preparation method of the present invention is a process of sintering and cooling the modified intermediate to obtain the final product. Optionally, the calcination temperature is 240-280°C, the sintering time is 18-22 hours, the sintering heating rate is controlled at 1-5°C / min, and the sintering cooling process is natural cooling.

[0058] Furthermore, in order to accurately control the temperature and reduce the influence of temperature instability on the sintering effect, the heating rate of the sintering process in step (3) is controlled at 1 to 3°C / min, preferably 2°C / min, and the cooling process is natural cooling, so that a single-crystal high-nickel ternary positive electrode material with an island-like coating structure can be obtained.

[0059] The single crystal high nickel ternary positive electrode material of the present invention reduces the loss of active lithium ions of the high nickel positive electrode material during the first cycle of charge and discharge cycles by in-situ coating the titanate ferroelectric nanomaterial on the surface of the single crystal high nickel ternary positive electrode material matrix, and significantly improves the first cycle coulomb efficiency of the high nickel ternary material. Moreover, due to the ferroelectric effect of the titanate ferroelectric nanoparticles, the single crystal high nickel ternary positive electrode material of the present invention forms an interface electric field from top to bottom along the particle surface, provides a special lithium ion transmission path, reduces the interface degradation of the matrix high nickel ternary material, and significantly improves the cycle stability of the high nickel ternary material.

[0060] The following examples are used to illustrate the preparation of single crystal high nickel ternary positive electrode materials.

[0061] Example 1

[0062] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0063] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 550°C and calcined for 5h, and then continued to be heated to 750°C and calcined for 12h. The heating rate was maintained at 2°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0064] (2) Dissolve 0.01 mol of TiO2 and 0.01 mol of Ba(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.9 Co 0.05 Mn 0.05 The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate;

[0065] (3) placing the modified intermediate obtained in step (2) in a tube furnace, heating to 260°C at 2°C / min and calcining for 20h, then naturally cooling to room temperature, maintaining an air atmosphere in the tube furnace, and obtaining a modified single crystal ternary cathode material BaTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0066] BaTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 105°C for 4h; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0067] The modified high-nickel ternary positive electrode material obtained in this example was characterized and tested. Figure 1,The scanning electron microscope image of the ternary positive electrode material prepared in Example 1 shows the morphology and surface element composition of the material. The positive electrode material is a single crystal structure, and Ba and Ti coating elements exist on the surface. Figure 2 The interface coating of the ternary cathode material prepared in Example 1 is shown in Figure 1. The surface is an island-shaped coating structure with a coating structure thickness of 10-60 nm. The PFM test results of the ternary cathode material prepared in Example 1 are shown in Figure 1. Figure 3 As shown, it can be determined that the material has ferroelectric effect. Figure 4 The XRD phase characterization results shown in the figure show that the ternary cathode material prepared in Example 1 is a layered structure. The first cycle charge and discharge performance and the cycle performance of the ternary cathode material prepared in Example 1 are shown in Figure 2. Figure 5 and Figure 6 shown, specifically, Figure 5 It is a comparison chart of the capacity-voltage curves of the first cycle charge and discharge of the single crystal ternary positive electrode material of Example 1 of the present invention and the material prepared in the comparative example within the voltage range of 2.95-4.3V and activated at a rate of 0.1C, Figure 6 This is a comparison chart of the cycle performance of the single crystal ternary positive electrode material of Example 1 of the present invention and the material prepared in the comparative example within the voltage range of 2.95-4.3V and at a rate of 1C. Figure 5 and Figure 6 It can be seen that the first-cycle Coulomb efficiency of the material is 96.2%, and the 100-cycle retention rate is 88.9%.

[0068] Example 2

[0069] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0070] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 550°C and calcined for 5h, and then continued to be heated to 750°C and calcined for 12h. The heating rate was maintained at 2°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0071] (2) Dissolve 0.01 mol of TiO2 and 0.01 mol of Sr(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.9 Co 0.05 Mn0.05 The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate.

[0072] (3) placing the modified intermediate obtained in step (2) in a tube furnace, heating to 260°C at 2°C / min and calcining for 20h, then naturally cooling to room temperature, maintaining an air atmosphere in the tube furnace, and obtaining a modified single crystal ternary cathode material SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0073] SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 105°C for 4h; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0074] The SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 The assembled battery with O2 as the positive electrode material is characterized and tested. The positive electrode material is a single crystal structure, with Ba and Ti coating elements on the surface. From the perspective of interface coating, the surface is an island coating structure with a thickness of 5-80nm. The first cycle charge and discharge of the material is as follows Figure 7 As shown, specifically, it is a comparison diagram of the first-cycle charge and discharge capacity-voltage curve of the material activated at a rate of 0.1C in the voltage range of 2.95-4.3V, and the first-cycle coulomb efficiency is 94.3%. Figure 8 It is a comparison chart of the cycle performance of the single crystal ternary positive electrode material of Example 2 of the present invention and the material prepared in the comparative example at a voltage range of 2.95-4.3V and a rate of 1C, and the cycle retention rate after 100 cycles is 90.8%.

[0075] Example 3

[0076] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0077] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 510°C and calcined for 6 hours, and then heated to 710°C and calcined for 14 hours. The heating rate was maintained at 1°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0078] (2) Dissolve 0.01 mol of TiO2 and 0.01 mol of Sr(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.9 Co 0.05 Mn 0.05 The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate.

[0079] (3) The modified intermediate obtained in step (2) is placed in a tube furnace, heated to 250°C at 3°C / min and calcined for 19h, then naturally cooled to room temperature, and the air atmosphere is maintained in the tube furnace to obtain a modified single crystal ternary cathode material SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0080] SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 600r / min for 3 hours to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for drying for 3 hours; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 125°C for 3 hours; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0081] The SrTiO3@LiNi obtained in this example 0.9 Co 0.05 Mn 0.05 Performance testing of the assembled battery with O2 as the positive electrode material showed that the first-cycle coulomb efficiency was 94.2% and the 100-cycle retention rate was 88.2%.

[0082] Example 4

[0083] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0084] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 560°C and calcined for 5h, and then continued to be heated to 725°C and calcined for 15h. The heating rate was maintained at 3°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single crystal LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0085] (2) Dissolve 0.01 mol of TiO2 and 0.01 mol of Sr(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.9 Co 0.05 Mn 0.05The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate.

[0086] (3) The modified intermediate obtained in step (2) is placed in a tube furnace, heated to 265°C at 4°C / min and calcined for 22h, then naturally cooled to room temperature, and the air atmosphere is maintained in the tube furnace to obtain a modified single crystal ternary cathode material SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0087] The positive electrode material SrTiO3@LiNi prepared in step (3) 0.9 Co 0.05 Mn 0.05 O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 105°C for 4h; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0088] The SrTiO3@LiNi 0.9 Co 0.05 Mn 0.05 Performance testing of the assembled battery with O2 as the positive electrode material showed that the first-cycle coulomb efficiency was 96.4% and the 100-cycle retention rate was 89.1%.

[0089] Example 5

[0090] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0091] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.98 Co 0.01 Mn 0.01The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 580°C and calcined for 4 hours, and then continued to heat to 770°C and calcined for 11 hours. The heating rate was maintained at 2°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.98 Co 0.01 Mn 0.01 O2 cathode material;

[0092] (2) Dissolve 0.005 mol of TiO2 and 0.005 mol of Sr(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.98 Co 0.01 Mn 0.01 The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate;

[0093] (3) The modified intermediate obtained in (2) was placed in a tube furnace, heated to 245°C at 1°C / min and calcined for 21h, then naturally cooled to room temperature. The air atmosphere was maintained in the tube furnace to obtain the modified single crystal ternary cathode material 0.5SrTiO3@LiNi 0.98 Co 0.01 Mn 0.01 O2.

[0094] 0.5SrTiO3@LiNi 0.98 Co 0.01 Mn 0.01 O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 105°C for 4h; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator. 0.98 Co 0.01 Mn 0.01 The battery is assembled with O2 as the positive electrode, with a first-cycle coulomb efficiency of 93.9% and a 100-cycle cycle retention rate of 89%.

[0095] Example 6

[0096] In combination with a specific example, a high-nickel ternary positive electrode material with high initial efficiency and a preparation method thereof of the present invention are described, which is specifically prepared by the following steps:

[0097] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 505°C and calcined for 6 hours, and then continued to heat to 800°C and calcined for 10 hours. The heating rate was maintained at 5°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥99%, thus obtaining single-crystalline LiNi 0.98 Co 0.01 Mn 0.01 O2 cathode material;

[0098] (2) Dissolve 0.015 mol of TiO2 and 0.015 mol of Sr(OH)2 in 50 ml of anhydrous ethanol solution and disperse them evenly. 0.98 Co 0.01 Mn 0.01 The O2 positive electrode material is added to the dispersed solution and stirred to mix evenly; the mixed solution is placed in a constant temperature water bath at 80°C, stirred, heated and evaporated to dryness, and the evaporated product is scraped to obtain the modified material intermediate;

[0099] (3) The modified intermediate obtained in step (2) is placed in a tube furnace, heated to 280°C at 5°C / min and calcined for 18 hours, then naturally cooled to room temperature, and the air atmosphere is maintained in the tube furnace to obtain a modified single crystal ternary cathode material 1.5SrTiO3@LiNi 0.98 Co 0.01 Mn 0.01 O2.

[0100] 1.5SrTiO3@LiNi 0.98 Co 0.01 Mn 0.01O2, conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a black slurry; the slurry is then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h; the punched sheets are taken out to prepare pole pieces with a diameter of 12mm, which are then dried in a vacuum drying oven at 105°C for 4h; the pole pieces are placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries are assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator. 0.98 Co 0.01 Mn 0.01 The battery was assembled with O2 as the positive electrode, and the first-cycle coulomb efficiency was measured to be 91.8% and the 100-cycle retention rate was 87.3%.

[0101] Comparative Example 1

[0102] In terms of molar ratio, weigh appropriate amounts of battery-grade lithium hydroxide and commercial single-crystal Ni according to the ratio of Li:(Ni+Co+Mn)=1.06:1. 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 550°C and calcined for 5h, and then continued to be heated to 750°C and calcined for 12h. The heating rate was maintained at 2°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material (denoted as LiNi 0.9 Co 0.05 Mn 0.05 O2-1).

[0103] LiNi 0.9 Co 0.05 Mn 0.05O2-1 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 105°C for 4 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0104] The LiNi obtained in this comparative example 0.9 Co 0.05 Mn 0.05 O2-1 positive electrode material is characterized and tested. XRD phase characterization of the material is as follows Figure 4 As shown, it is a typical α-NaFeO2 phase layered structure; the first cycle charge and discharge of the material is as follows Figure 5 As shown, the first cycle coulomb efficiency is 86.9%; the cycling performance of the material is shown Figure 6 As shown, the 100-cycle retention rate is 76.1%.

[0105] Comparative Example 2

[0106] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 550°C and calcined for 5h, and then continued to be heated to 750°C and calcined for 12h. The heating rate was maintained at 2°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0107] (2) Take 0.1 mol of LiNi 0.9 Co 0.05 Mn 0.05 The O2 positive electrode material is added and dispersed in the anhydrous ethanol solution, and stirred to disperse evenly; the mixed solution is placed in a constant temperature water bath pot at 80°C, stirred and heated to evaporate to dryness, and the evaporated product is scraped off.

[0108] (3) The dried intermediate product obtained in step (2) was placed in a tube furnace, heated to 260° C. at 2° C. / min and calcined for 20 h, then naturally cooled to room temperature, and the air atmosphere was maintained in the tube furnace to obtain single crystal LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material (denoted as LiNi 0.9 Co 0.05 Mn 0.05 O2-2).

[0109] Compared with LiNi 0.9 Co 0.05 Mn 0.05 O2-2 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 105°C for 4 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0110] The LiNi obtained in this comparative example 0.9 Co 0.05 Mn 0.05 The assembled battery with O2-2 as the positive electrode material was characterized and tested, and the XRD phase characterization of the material was measured as follows Figure 4 As shown, it is a typical α-NaFeO2 phase layered structure; the first cycle charge and discharge of the material is as follows Figure 5 As shown, the first cycle coulomb efficiency is 87.4%; the cycling performance of the material is shown Figure 6 As shown, the 100-cycle retention rate is 72.8%.

[0111] Combination Figure 5The battery capacity-voltage curve of the first cycle of charge and discharge shows that in the charging stage, the voltage changes of Example 1 of the present invention and Comparative Examples 1 and 2 are not significantly different. However, in the discharging stage, the capacity changes of Example 1 and the two comparative examples show obvious differences. Therefore, the difference can be seen by calculating the first cycle coulomb efficiency of the positive electrode material of Example 1 and the two comparative examples. Compared with the first cycle coulomb efficiency of 87% of the two comparative examples, the first cycle coulomb efficiency of Example 1 of the present invention is significantly improved, reaching 96.2%.

[0112] Combination Figure 6 From the cycle capacity curve of the battery, it can be seen that the slopes of the curves of comparative examples 1 and 2 are relatively large, and the shape of the discharge curve of embodiment 1 of the present invention is relatively gentle, indicating that the capacity decay rate of the comparative battery is relatively fast, and the capacity decay rate of the battery of embodiment 1 of the present invention is relatively slow, and the cycle life of the battery of embodiment 1 of the present invention is longer.

[0113] Combination Figures 5 to 8 By comparison, it can be seen that whether it is titanium-based Ba salt or titanium-based Sr salt as the coating modified material, the single crystal ternary positive electrode material obtains better first-cycle coulomb efficiency and battery cycle life after modification.

[0114] Therefore, the present invention can reduce the active Li+ in the first cycle of the single crystal ternary positive electrode material by coating the positive electrode material matrix with in-situ ferroelectric nanomaterials based on the intrinsic ferroelectric effect of the ferroelectric material. + The loss is conducive to the formation of a specific ion transmission pathway, thereby significantly improving the first-cycle coulombic efficiency and cycle stability of the positive electrode material.

[0115] Comparative Example 3

[0116] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 510°C and calcined for 6 hours, and then heated to 710°C and calcined for 14 hours. The heating rate was maintained at 1°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0117] (2) Take 0.1 mol of LiNi 0.9 Co 0.05 Mn 0.05The O2 positive electrode material is added and dispersed in the anhydrous ethanol solution, and stirred to disperse evenly; the mixed solution is placed in a constant temperature water bath pot at 80°C, stirred and heated to evaporate to dryness, and the evaporated product is scraped off.

[0118] (3) The dried intermediate product obtained in step (2) was placed in a tube furnace, heated to 250°C at 3°C / min and calcined for 19h, then naturally cooled to room temperature, and the air atmosphere was maintained in the tube furnace to obtain single crystal LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material (denoted as LiNi 0.9 Co 0.05 Mn 0.05 O2-3).

[0119] LiNi 0.9 Co 0.05 Mn 0.05 O2-3 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 600 r / min for 3 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for drying for 3 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 125°C for 3 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0120] The LiNi obtained in this comparative example 0.9 Co 0.05 Mn 0.05 Performance testing of the assembled battery using O2-3 as the positive electrode material showed that the first-cycle coulomb efficiency was 86% and the 100-cycle retention rate was 75.5%.

[0121] Comparative Example 4

[0122] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.9 Co 0.05 Mn 0.05The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 560°C and calcined for 5h, and then continued to be heated to 725°C and calcined for 15h. The heating rate was maintained at 3°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single crystal LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material.

[0123] (2) Take 0.1 mol of LiNi 0.9 Co 0.05 Mn 0.05 The O2 positive electrode material is added and dispersed in the anhydrous ethanol solution, and stirred to disperse evenly; the mixed solution is placed in a constant temperature water bath pot at 80°C, stirred and heated to evaporate to dryness, and the evaporated product is scraped off.

[0124] (3) The dried intermediate product obtained in step (2) was placed in a tube furnace, heated to 265° C. at 4° C. / min and calcined for 22 h, then naturally cooled to room temperature, and the air atmosphere was maintained in the tube furnace to obtain single crystal LiNi 0.9 Co 0.05 Mn 0.05 O2 positive electrode material (denoted as LiNi 0.9 Co 0.05 Mn 0.05 O2-4).

[0125] LiNi 0.9 Co 0.05 Mn 0.05 O2-4 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 600 r / min for 3 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for drying for 3 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 125°C for 3 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator.

[0126] The LiNi obtained by this ratio 0.9 Co 0.05 Mn 0.05The performance of the assembled battery with O2-4 as the positive electrode was tested, and the first-cycle coulomb efficiency was measured to be 87.1% and the 100-cycle retention rate was 73%.

[0127] Comparative Example 5

[0128] (1) According to the molar ratio of Li:(Ni+Co+Mn)=1.06:1, weigh an appropriate amount of battery-grade lithium hydroxide and commercial single-crystal Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 580°C and calcined for 4 hours, and then heated to 770°C and calcined for 11 hours. The heating rate was maintained at 1°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥95%, thus obtaining single-crystalline LiNi 0.98 Co 0.01 Mn 0.01 O2 positive electrode material.

[0129] (2) Take 0.1 mol of LiNi 0.98 Co 0.01 Mn 0.01 The O2 positive electrode material is added and dispersed in the anhydrous ethanol solution, and stirred to disperse evenly; the mixed solution is placed in a constant temperature water bath pot at 80°C, stirred and heated to evaporate to dryness, and the evaporated product is scraped off.

[0130] (3) The dried intermediate product obtained in step (2) was placed in a tube furnace, heated to 265° C. at 4° C. / min and calcined for 22 h, then naturally cooled to room temperature, and the air atmosphere was maintained in the tube furnace to obtain single crystal LiNi 0.98 Co 0.01 Mn 0.01 O2 positive electrode material (denoted as LiNi 0.98 Co 0.01 Mn 0.01 O2-5).

[0131] LiNi 0.98 Co 0.01 Mn 0.01O2-5 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 600 r / min for 3 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for drying for 3 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 125°C for 3 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator. 0.98 Co 0.01 Mn 0.01 O2-5 is a positive electrode assembled battery, and the first cycle coulomb efficiency was measured to be 73% and the 100-cycle cycle retention rate was 66.7%.

[0132] Comparative Example 6

[0133] In terms of molar ratio, weigh appropriate amounts of battery-grade lithium hydroxide and commercial single-crystal Ni according to the ratio of Li:(Ni+Co+Mn)=1.06:1. 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor was uniformly mixed; the mixture was placed in a tube furnace, heated to 505°C and calcined for 6 hours, and then continued to heat to 800°C and calcined for 10 hours. The heating rate was maintained at 5°C / min throughout the process, and the oxygen concentration in the tube furnace was maintained at ≥99%, thus obtaining single-crystalline LiNi 0.98 Co 0.01 Mn 0.01 O2 positive electrode material.

[0134] (2) Take 0.1 mol of Li Ni 0.98 Co 0.01 Mn 0.01 The O2 positive electrode material is added and dispersed in the anhydrous ethanol solution, and stirred to disperse evenly; the mixed solution is placed in a constant temperature water bath pot at 80°C, stirred and heated to evaporate to dryness, and the evaporated product is scraped off.

[0135] (3) The dried intermediate product obtained in step (2) was placed in a tube furnace, heated to 280° C. at 5° C. / min and calcined for 18 h, then naturally cooled to room temperature, and the air atmosphere was maintained in the tube furnace to obtain single crystal LiNi 0.98 Co 0.01 Mn 0.01O2 positive electrode material (denoted as LiNi 0.98 Co 0.01 Mn 0.01 O2-6).

[0136] LiNi 0.98 Co 0.01 Mn 0.01 O2-6 was mixed evenly with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was used as solvent. The mixture was placed in a small beaker and stirred at a speed of 600 r / min for 3 hours to obtain a black slurry; the slurry was then coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for drying for 3 hours; the punched sheets were taken out to prepare pole pieces with a diameter of 12 mm, and then dried in a vacuum drying oven at 125°C for 3 hours; the pole pieces were placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.1 ppm for 4 hours to reduce the moisture adsorbed by the pole pieces during the transfer process; finally, the CR2032 button batteries were assembled in the glove box. A circular lithium metal sheet with a diameter of 14 mm was used as the negative electrode, 1 mol / L LiPF6 (EC / DMC=1:1) was used as the electrolyte, and a polyolefin porous membrane with a diameter of 16 mm was used as the separator. 0.98 Co 0.01 Mn 0.01 O2-6 is a positive electrode assembled battery with a first-cycle coulombic efficiency of 79% and a 100-cycle cycle retention rate of 68.9%.

[0137] Effect comparison

[0138] The preparation process parameters and performance test results of Examples 1 to 6 are shown in Table 1.

[0139] Table 1

[0140]

[0141] The preparation process parameters and performance test results of Comparative Examples 1 to 6 are shown in Table 2.

[0142] Table 2

[0143]

[0144]

[0145] The positive electrode materials prepared in Examples 1 to 6 of the present invention have higher first-cycle coulombic efficiency than the positive electrode materials prepared in Comparative Examples 1 to 6. The first-cycle coulombic efficiency of the positive electrode materials in the examples is stable at more than 90%, and the subsequent cycle stability is also significantly improved.

[0146] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. A single crystal ternary cathode material, characterized in that: The single crystal ternary positive electrode material comprises a single crystal ternary positive electrode material matrix and a coating structure, wherein the coating structure is a titanate ferroelectric nanomaterial, and the titanate ferroelectric nanomaterial is coated on the surface of the single crystal ternary positive electrode material matrix.

2. The single crystal ternary cathode material according to claim 1, characterized in that: The coating structure is coated on the surface of the single crystal ternary positive electrode material substrate in an island shape, and the thickness of the coating structure is 1-100 nm.

3. The single crystal ternary cathode material according to claim 1, characterized in that: The chemical formula of the single-crystal ternary cathode material is MTiO3@LiNi x Co y Mn z O2, where in terms of molar ratio, 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1–x–y, and M is selected from at least one of Ba and Sr.

4. A method for preparing a single crystal ternary cathode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) fully mixing a single crystal hydroxide precursor and lithium hydroxide, placing the mixture in a tube furnace, sintering the mixture in an oxygen atmosphere, and cooling the mixture to obtain a single crystal ternary cathode material matrix; (2) uniformly dispersing the titanate ferroelectric nanomaterial reactant in an organic solvent, adding the single crystal ternary cathode material matrix and mixing evenly, and then fully evaporating to dryness under a water bath heating and stirring environment to obtain a modified intermediate product; (3) placing the modified intermediate product in a tubular furnace for sintering, and obtaining the single crystal ternary positive electrode material after natural cooling, wherein the surface of the single crystal ternary positive electrode material is the titanate ferroelectric nanomaterial coating structure.

5. The preparation method according to claim 4, characterized in that: The chemical formula of the single-crystalline hydroxide precursor described in step (1) is Ni x Co y Mn z (OH)2, and in terms of molar ratio, 0.9 ≤ x < 1.0, 0 < y ≤ 0.05, z = 1 – x – y. The particle size distribution of the single-crystalline hydroxide precursor is 10.0 μm ≤ d (50) ≤ 11.5 μm .

6. The preparation method according to claim 4, characterized in that: The sintering in an oxygen atmosphere in step (1) is a two-stage sintering in an oxygen-containing atmosphere, wherein the concentration of oxygen in the oxygen-containing atmosphere is not less than 95%, and the two-stage sintering comprises: first sintering at 500-600°C for 4-6h, and then sintering at 700-800°C for 10-16h, and the temperature rise and fall rate during the two-stage sintering process is 1-5°C / min.

7. The preparation method according to claim 4, characterized in that: The reactants of the titanate ferroelectric nanomaterial in step (2) are titanium-containing compounds and alkaline earth metal compounds, and the organic solvent is an anhydrous ethanol solution.

8. The preparation method according to claim 7, characterized in that: The titanium-containing compound is selected from at least one of TiO2, Ti(NO3)4, and Ti(BH4)2.

9. The preparation method according to claim 7, characterized in that: The alkaline earth metal compound is selected from one or more of Ba(OH)2, BaCO3, Sr(OH)2, and SrCO3.

10. The preparation method according to claim 7, characterized in that: In the titanium-containing compound and the alkaline earth metal compound, the molar ratio of titanium ions to alkaline earth metal ions is 1:

1.

11. The preparation method according to claim 5, characterized in that: The molar ratio of the sum of nickel ions, cobalt ions and manganese ions to titanium ions in the single crystal ternary positive electrode material satisfies 1:(0.5%-1.5%).

12. The preparation method according to claim 4, characterized in that: In step (3), the calcination temperature is 240-280° C., the sintering heating rate is 1-5° C. / min, the sintering cooling process is natural cooling, and the sintering duration is 18-22 hours.

Citation Information

Patent Citations

  • Preparation method of strontium titanate coated single crystal nickel-rich ternary positive electrode material

    CN113293441A

  • High-nickel single-crystal nickel-cobalt-aluminum ternary positive electrode material and preparation method thereof

    CN113422046A

  • High-voltage and high-rate composite positive electrode material and preparation method and application thereof

    CN113707865A

  • Bimetal-doped ternary positive electrode material coated with barium strontium titanate and preparation method of bimetal-doped ternary positive electrode material

    CN116282220A

  • Preparation method of high-nickel single-crystal ternary positive electrode material

    CN118738367A